Critical behavior in the inhomogeneous ferromagnet SrFe0.80Co0.20O3.0 - Lago, J; Rosseinsky, M; Blundell, S; Battle, P; Diaz, M; Uriarte, I; Rojo, T (2011)
A detailed muon spin relaxation (μSR) and magnetization study is presented of the paramagnetic-to-ferromagnetic transition in the compound SrFe0.80Co0.20O3. The critical exponents derived from the static critical analysis are close to the theoretical predictions for the Heisenberg model in three dimensions. However, a small drift toward mean-field values is interpreted as arising from the presence of long-range dipolar interactions between the Fe(IV) centers. The evolution of spin dynamics across the transition determined from the μSR study is consistent with this interpretation. μSR and magnetization data also provide evidence of an inhomogeneous magnetic state both above and below Tc, placing this system in line with other double-exchange materials such as manganites and cobaltites where spontaneous electronic and magnetic phase separation appears conspicuous and explains much of the encountered experimental phenomenology. © 2011 American Physical Society.